Study of Prevalence and Risk Factors of Asthma and Allergic Diseases Among School Children (6-7 and 13-14 years) Based on ISAAC Protocol in Jam City, Bushehr Province in 2014 - Tahere Assadi; Mohammadkazem Gheybi; Afshin Shirkani; Ali Movahed; Shaghaeagh Khoddami; Ahmad Ashourinejad; Shokroola Farrokhi (Iranian South Medical Journal, 2017)
Background: Asthma and allergic diseases are raised as a major health problem in the world. The prevalence of these diseases is on the rise specifically in the world and Iran. Accordingly, the aim of this study was to assess the prevalence of these diseases in Jam City, from environs of Bushehr Province.